The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s00784-016-1944-7
|View full text |Cite
|
Sign up to set email alerts
|

Do periapical and periodontal pathologies affect Schneiderian membrane appearance? Systematic review of studies using cone-beam computed tomography

Abstract: Incidental maxillary sinus findings on CBCT scans warrant thorough differential diagnosis. Frequently, they may be related to dental pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 73 publications
2
19
0
1
Order By: Relevance
“…Previous literature reported that the presence of periapical infection resulted in an increase in the thickness of the mucosa in 38.1%–83.2% of cases. [ 9 10 11 12 ] This correlation was confirmed by Eggmann et al [ 26 ] who reported in their systematic review that periapical lesions in the maxillary posterior aspect, but not periodontal pathology, are correlated with SMT. Further, Dagassan-Berndt et al [ 27 ] noted that although clinical signs of periodontal destruction were not associated with SMT in dentulous individuals, periapical pathologies and the distance from root tips to the maxillary antrum showed a significant correlation.…”
Section: Discussionmentioning
confidence: 57%
“…Previous literature reported that the presence of periapical infection resulted in an increase in the thickness of the mucosa in 38.1%–83.2% of cases. [ 9 10 11 12 ] This correlation was confirmed by Eggmann et al [ 26 ] who reported in their systematic review that periapical lesions in the maxillary posterior aspect, but not periodontal pathology, are correlated with SMT. Further, Dagassan-Berndt et al [ 27 ] noted that although clinical signs of periodontal destruction were not associated with SMT in dentulous individuals, periapical pathologies and the distance from root tips to the maxillary antrum showed a significant correlation.…”
Section: Discussionmentioning
confidence: 57%
“…nature of periapical lesions, it is crucial to use the highest resolution possible so that posterior maxillary teeth, alveolar process and floor of the maxillary sinus can be evaluated efficiently. Accordingly, otolaryngologists should be informed about the odontogenic source of maxillary sinusitis and work with dentists for correct imaging, diagnosis and the treatment of mucosal thickening associated with periapical lesion (s) (Eggmann et al 2017). Nevertheless, it should be remembered that CBCT uses ionizing radiation and must be preferred as a diagnostic tool in cases where two-dimensional images and clinical examination alone are unable to provide enough information for identifying odontogenic sources of sinus disease.…”
Section: Amount Of Mt N (%)mentioning
confidence: 99%
“…The majority of previous studies have focused only on the relationship between maxillary sinus mucosal thickening and alveolar bone loss instead of on residual alveolar bone height. 15 Although conventional computed tomography examination was considered the gold standard for sinus visualization and diagnostic procedures, cone-beam computed tomography (CBCT) recently has been used widely for imaging studies of dental and maxillofacial regions. 16 CBCT imaging offers lower radiation dosage, shorter scanning time, higher image resolution, and lower cost compared to traditional CT. 17 CBCT was proven to be reliable for the evaluation of structures in the maxillary sinus, as well as periapical and periodontal alveolar bone changes.…”
Section: Introductionmentioning
confidence: 99%
“…reported a significant correlation between maxillary sinus mucosal thickening and alveolar bone loss. The majority of previous studies have focused only on the relationship between maxillary sinus mucosal thickening and alveolar bone loss instead of on residual alveolar bone height 15 …”
Section: Introductionmentioning
confidence: 99%